Multiple mechanisms enable broad-spectrum activity of the Pelargonium sidoides root extract EPs 7630 against acute respiratory tract infections - Cinatl, Jindrich; Wass, Mark N.; Michaelis, Martin (Frontiers in Pharmacology, 2024)
There is clinical evidence showing that the Pelargonium sidoides root extract EPs 7630 is a safe and effective treatment for a range of acute infectious respiratory illnesses. Moreover, EPs 7630 has been shown to reduce the use of antibiotics, which is important in the context of rising antibiotic resistance levels. A wide range of mechanisms appears to contribute to the beneficial effects of EPs 7630, e.g. antibacterial, antiviral, immunomodulatory, and epithelial barrier effects. This broad spectrum of pharmacological activities seems to enable the clinical activity of EPs 7630 against multiple respiratory infections. In particular, the combination of antiviral and immunomodulatory effects may enable EPs 7630 to tackle acute viral respiratory infections both in early stages of the disease process, which are driven by virus replication, as well as in later stages, which are caused by an overshooting immune response. Hence, EPs 7630 is a prime example of a plant extract with evidence-based clinical efficacy, including a solid understanding of the underlying mechanisms of action. The example of EPs 7630 demonstrates that plant extracts have a potential role as evidence-based clinical treatments and that they deserve pre-clinical and clinical testing and investigation in the same way as any other drug class.